The Formation Of The Contempt Of Court Law To Maintain The Dignity Of Peradi And Indonesia - Siti Rahmawati Djula (Universitas Negeri Gorontalo, 2019)
Abstract: The purpose of this research is to analyze rule idea contempt of court in the law as a form of obedience to maintain the dignity of the Indonesian judiciary It is often found that many visitors in a court process make actions that do not respect the course of the trial, such actions can be categorized as criminal acts against the judicial process or what is known as contempt of court Contempt of court in Indonesia has not been regulated in an integrated manner in one legislation, so based on that this research was conducted with the hope of getting the best solution in concocting the idea of contempt of court . to strengthen compliance in the Indonesian judiciary This type of research is normative legal research with a statutory approach , a conceptual approach, a comparative approach an nd a case approach. The analysis used in this research is deductive data analysis using a qualitative approac . Based on the results of the study, the answers to the existing problems were obtained, that a Contempt Of Court arrangement was needed separately in aaw, this is intended to uphold dithe gnity and ensure the judicial process runs without interference or threats from various parties. While the regulation on CoC can only be found in a few norms that seem separate, act it is s, till very biased when the regulation of the same act is regulated based on different regulations, with unclear procedures, so that specific and comprehensivearrangementse needed to be related to the Contempt Of action . Court through the idea of the Contempt Of Court Act The presence of the Contempt Of Court Law can bebe newope for the face of judicial power in Indonesia.Keywords: Rules Idea, Contempt Of Court , Judicial Obedience